(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
The TP53 gene, widely known as the “guardian of the genome,” is the most frequently mutated tumor suppressor in human cancer, with missense mutations—predominantly found in the DNA-binding domain—accounting for nearly 90% of total alterations. This review synthesizes contemporary findings from 2022–2025 regarding the structural organization of the TP53 gene, its dominant hotspot mutations (including R175H, R273H, and R248Q), and their cancer-type-specific prevalence and clinical consequences. Advanced bioinformatic analyses, cryo-EM structural reconstructions, and COSMIC/IARC database insights have revealed that TP53 mutagenesis is strongly driven by protein structural instability, especially in the central DNA-binding domain. We highlight how DNA-contact and structural/destabilizing mutants differ in their oncogenic mechanisms and drug resistance profiles, with R273H demonstrating the strongest association with metastasis and therapy resistance. Recent developments in precision oncology—including p53 reactivators, synthetic lethality strategies, and CRISPR-based gene correction—underscore growing therapeutic potential against TP53-mutant cancers. This review emphasizes the necessity for mutation-specific treatment strategies and the integration of AI-driven bioinformatics to guide precision medicine in the TP53 era.